THE IMPACT OF TRAUMATIC EXPERIENCES TO SEO JIN-WOO CHARACTER IN REMEMBER KOREAN DRAMA - Benazir Isna; Bima Prana Chitra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
THE IMPACT OF TRAUMATIC EXPERIENCES TO SEO JIN-WOO CHARACTER IN REMEMBER KOREANDRAMABenazir Isna 1, Dr. Bima Prana Chitra M. Hum 2Fakultas Bahasa dan KomunikasiUniversitas Harapan MedanEmail: isnabena11@gmail.comAbstractThe objective of this research are characterization of Seo Jin Woo, impact of traumatic experience to SeoJin Woo, Psychoanalysis of Seo Jin Woo character and moral values presented in Remember drama. Thisresearch used descriptive qualitative research. The data of this research were script, character, anddrama on Remember (2015) as the source of data. This research focuses on characterization of Seo JinWoo Nurgiyantoro (1955), traumatic experience by Seo Jin Woo character based on DSM (1980),psychology of Seo Jin Woo character based on theory Sigmund Freud (1896), and moral values in dramaRemember based on Hurlock, Elizabeth ( 1972:386).Keywords: Characterization, Traumatic experience, Psychoanalysis, Moral